2016
DOI: 10.5693/djo.01.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of augmented tenotomy and reattachment in the infantile nystagmus syndrome

Abstract: Purpose-To test the hypothesis that augmented tenotomy and reattachment surgery (AT-R), which involves placing an additional suture in each distal tendon during the 4-muscle tenotomy and reattachment (T-R) or other infantile nystagmus syndrome (INS) procedures, could increase the beneficial effects of many types of extraocular muscle (EOM) surgery to treat INS.Methods-Both infrared reflection and high-speed digital video systems were used to record the eye movements in 4 patients with INS before and after AT-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…8 We measured fixation stability in these animals at the different time points and found a temporary improvement in fixation stability of the treated eye when the untreated eye was viewing but no consistent changes when the treated eye was viewing. Dell'Osso et al suggested that tenotomy surgery reduces nystagmus intensity 47,48 in humans with infantile nystagmus syndrome due to manipulation of proprioceptive receptors in the EOM. It is possible that similar mechanisms are at play following the strabismus correction surgery that we performed, although another study that attempted tenotomy surgery in monkeys with infantile nystagmus showed inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…8 We measured fixation stability in these animals at the different time points and found a temporary improvement in fixation stability of the treated eye when the untreated eye was viewing but no consistent changes when the treated eye was viewing. Dell'Osso et al suggested that tenotomy surgery reduces nystagmus intensity 47,48 in humans with infantile nystagmus syndrome due to manipulation of proprioceptive receptors in the EOM. It is possible that similar mechanisms are at play following the strabismus correction surgery that we performed, although another study that attempted tenotomy surgery in monkeys with infantile nystagmus showed inconsistent results.…”
Section: Discussionmentioning
confidence: 99%